CAMEL Analysis on performance of Asean Public Listed Banks - Rossazana Ab-Rahim, Ab-Rahim; Norlina, Kadri; Chin, Amy Ee Ling; Abdul Alim, Dee (Canadian Center of Science and Education, 2018)
The study is conducted to measure the performance of public listed banks in five ASEAN countries. This study covers 63 public listed banks from Malaysia, Singapore, Thailand, and the Philippines over the period of 1997 to 2011. The CAMEL analysis which is based on Capital Adequacy, Asset Quality, Management Efficiency, Earning Quality, and Liquidity is employed in this study. The objectives of the study are to measure the performance of public listed banks as well as to compare the performance across countries. The results of the CAMEL analysis show that Singaporean public listed banks are the top performer as compared to their counterparts. Next, the comprehensive results reveal that Public Bank in Malaysia, United Overseas Bank in Singapore, Bank ArthaGraha in Indonesia, Bank of Ayudhya in Thailand and Union Bank of the Philippines are the top performed banks.